2010
DOI: 10.1152/jn.00028.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Frequency, Timing, and Intensity Cues in a Complex Acoustic Categorization Task

Abstract: Nagel KI, McLendon HM, Doupe AJ. Differential influence of frequency, timing, and intensity cues in a complex acoustic categorization task. J Neurophysiol 104: 1426 -1437, 2010. First published July 7, 2010 doi:10.1152/jn.00028.2010. Songbirds, which, like humans, learn complex vocalizations, provide an excellent model for the study of acoustic pattern recognition. Here we examined the role of three basic acoustic parameters in an ethologically relevant categorization task. Female zebra finches were first tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 67 publications
(75 reference statements)
6
28
0
Order By: Relevance
“…In behavioral experiments, we found that birds were able to discriminate time-warped stimuli up to a factor of two significantly over chance level. These data are consistent with a recent behavioral study in female birds (Nagel et al 2010). This behavioral capacity motivated the search for an underlying neural basis for time-warp invariance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In behavioral experiments, we found that birds were able to discriminate time-warped stimuli up to a factor of two significantly over chance level. These data are consistent with a recent behavioral study in female birds (Nagel et al 2010). This behavioral capacity motivated the search for an underlying neural basis for time-warp invariance.…”
Section: Discussionsupporting
confidence: 93%
“…We used the same pairs of songs for all subjects here, which leads to a possibility of pseudoreplication. However, in the previous study (Nagel et al 2010), a different set of songs was used and behavioral results were strikingly consistent with those here (for the subset of time warps tested).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There is, indeed, evidence that some songbirds are sensitive to variation in pitch, amplitude and song syllable duration in their natural song [11]. Also, some mammal and bird species show a sensitivity to the general prosodic patterns in human speech [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%